The Impact of Transferred COVID-19 on Sinonasal Symptoms in Patients with Chronic Polyposis Rhinosinusitis and Aspirin-Exacerbated Respiratory Disease - Moldovanov, Ivan; Zabolotna, Diana (The Ukrainian Scientific Medical Youth Journal, 2025)
chronic rhinosinusitis (CRS) is a prevalent disease affecting 5-15% of the population, characterized by prolonged inflammation of the mucosa of the paranasal sinuses. Chronic rhinosinusitis with nasal polyps (CRSwNP) accounts for approximately 18-20% of all CRS cases and has a more severe clinical course compared to CRS without nasal polyps (CRSsNP). A particular group of patients includes those with CRSwNP associated with aspirin-exacerbated respiratory disease (AERD), which comprises asthma, rhinosinusitis with polyps, and intolerance to nonsteroidal anti-inflammatory drugs (NSAIDs). This study aimed to evaluate the impact of a past COVID-19 infection on sinonasal symptoms and quality of life in patients with chronic polypous rhinosinusitis and aspirin triad based on the analysis of SNOT-22 questionnaire scores and endoscopic assessment results using the Lund-Kennedy scale. The study was conducted among outpatients at the clinic of the State Institution " O.S. Kolomiychenko Institute of Otolaryngology of National Academy of Sciences of Ukraine." Sixty patients aged 18 to 75 years with a diagnosis of chronic polypous rhinosinusitis with NSAID intolerance were selected and divided into two groups: Group 1 (17 patients) who did not have COVID-19 and Group 2 (43 patients) who had a history of COVID-19. Group 2 was further divided into two subgroups: Subgroup 2A (18 patients, who reported no impact of COVID-19 on the course of CRS) and Subgroup 2B (25 patients, who reported a subjective worsening of CRS after COVID-19). A survey was conducted using the SNOT-22 questionnaire, and endoscopic examination of the nasal cavity was performed with assessment using the Lund-Kennedy scale. The analysis of the SNOT-22 results showed that the mean scores in Group 1 were 41.9 ± 17.94, and in Group 2, they were 43.62 ± 20.12, with no statistically significant differences (p=0.812). The mean scores in Subgroups 2A and 2B were 44.3 ± 19.4 and 43.0 ± 21.2, respectively, also with no statistically significant differences (p=0.874). The endoscopic assessment using the Lund-Kennedy scale did not reveal significant differences between the groups (p=0.588). The study results indicate that a past COVID-19 infection did not have a statistically significant impact on sinonasal symptoms in patients with chronic polypous rhinosinusitis and aspirin triad. COVID-19 did not lead to a significant worsening of the clinical course of the disease, warranting further studies to explore the virus's impact on other aspects of respiratory health in patients with AERD.